Komitmen Terhadap Organisasi (Studi Pada Dosen dan Karyawan Pendukung Akademik di Universitas Swasta X Jakarta) - Widia Paramita; Sukmarani Sukmarani (Universitas Muhammadiyah Jember, 2023)
This study aims to analyze and explain the description of commitment to the organization of lecturers and academic support staff at DKI Jakarta private universities. This study uses a quantitative approach method, and the analysis technique was done by descriptive analysis. The subjects in this study were lecturers and employees at at DKI Jakarta private universities, with 432 participants consisting of 216 lecturer and 216 employees. The sampling technique used in this research is cluster random sampling. The scale used was organizational commitment. The results of this study have described that lecturers and employees at DKI Jakarta private universities have different commitments. The lecturers have affective commitment (AC) and employees have continuance commitment (CC).